2018
DOI: 10.1038/s41394-018-0058-7
|View full text |Cite
|
Sign up to set email alerts
|

Persistent urine leakage around a suprapubic catheter: the experience of a person with chronic tetraplegia

Abstract: IntroductionPersistent urine leakage after suprapubic cystostomy in tetraplegic subjects occurs due to shrinkage of the urinary bladder and bladder spasms. The patient’s social life is adversely affected as clothes become wet, smelly, and require frequent changing, thus increasing the workload of carers.Case presentationA 48-year-old male sustained C-4 complete (AIS:A) tetraplegia while swimming in 2007. Suprapubic cystostomy was performed in 2009. From 2012, this patient had urine leakage around the suprapubi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 6 publications
1
0
0
Order By: Relevance
“…As in previous studies, catheter-associated urinary tract infection (CA-UTI) was also the most common complications among patients with IUC, 56.8% [37]. In this study, the other complications that were reported and/or observed were leakage, blockage and bleeding, as reported elsewhere [37,43,44]. Leakage (11.9% vs. 0.8%) and blockage (10.4% vs. 0.0%) were the more frequently observed complications, compared to the others, and were significantly higher among patients with long-term IUC compared to those with short-term IUC (p = 0.005).…”
Section: Discussionsupporting
confidence: 77%
“…As in previous studies, catheter-associated urinary tract infection (CA-UTI) was also the most common complications among patients with IUC, 56.8% [37]. In this study, the other complications that were reported and/or observed were leakage, blockage and bleeding, as reported elsewhere [37,43,44]. Leakage (11.9% vs. 0.8%) and blockage (10.4% vs. 0.0%) were the more frequently observed complications, compared to the others, and were significantly higher among patients with long-term IUC compared to those with short-term IUC (p = 0.005).…”
Section: Discussionsupporting
confidence: 77%